2013
DOI: 10.3390/su5052191
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Climate Change among Adolescents: Implications for Subjective Well-Being and Environmental Engagement

Abstract: Abstract:The objective of this questionnaire study was to investigate how Swedish adolescents (n = 321) cope with climate change and how different coping strategies are associated with environmental efficacy, pro-environmental behavior, and subjective well-being. The results were compared to an earlier study on 12-year-olds, and the same coping strategies, problem-focused coping, de-emphasizing the seriousness of the threat, and meaning-focused coping, were identified. As in the study on children, problem-focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
199
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(215 citation statements)
references
References 61 publications
8
199
0
8
Order By: Relevance
“…Hence, this study extends the results from earlier studies that have found that de-emphasizing the seriousness of climate change goes together with a low degree of environmental efficacy (Ojala, 2012(Ojala, , 2013b to concern a more general feeling of low self-efficacy. This further emphasizes the importance of applying an -action competence approach‖ when educating about these issues, in order to help these young people to feel empowered (Jensen & Schnack, 1997;Mogensen & Schnack, 2010).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Hence, this study extends the results from earlier studies that have found that de-emphasizing the seriousness of climate change goes together with a low degree of environmental efficacy (Ojala, 2012(Ojala, , 2013b to concern a more general feeling of low self-efficacy. This further emphasizes the importance of applying an -action competence approach‖ when educating about these issues, in order to help these young people to feel empowered (Jensen & Schnack, 1997;Mogensen & Schnack, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…This result could perhaps be explained by theories and studies showing that if people do not know of any ways of solving a problem, i.e. feel less in control, they are also more inclined to cope with the problem in defensive ways (Ojala, 2013b;Folkman & Lazarus, 1980;Stern, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convém mencionar que já existem estudos dedicados à população adolescente e ao seu engajamento com questões ambientais (Kaiser et al, 2007;Renaud-Dubé et al, 2010;Wray-Lake et al, 2010;Ojala, 2013). Contudo, quando se trata especificamente da visão desse grupo sobre mudanças climáticas, o número de estudos existentes é ainda pequeno, tanto internacionalmente quanto no cená-rio nacional (Barros & Pinheiro, 2013).…”
Section: Introductionunclassified
“…Wray-Lake et al (2010) e Ojala (2013) ressaltam, por isso, a importância de conduzir pesquisas com adolescentes, principalmente ao considerar que serão eles os futuros cidadãos, sejam eles políticos, cientistas, empresários, professores, enfim, futuros adultos que irão lidar mais intensamente com os impactos das MCGs.…”
Section: Introductionunclassified